Effects of the differences between native and non-native English-speaking teachers on students' attitudes and motivation toward learning English. Issue 2 (3rd April 2017) - Pae, Tae-Il
Abstract: This study presents findings on three research agendas: (1) the difference between native English-speaking teachers (NESTs) and non-native English-speaking teachers (NNESTs) in students' attitudes toward and motivation for learning English, (2) the moderating effect of the type of class (i.e., English Conversation vs. Practical English) on the difference in students' perceived attitudes and motivation, and (3) the difference between NESTs and NNESTs in their self-perception of their teaching practices and the effect of the type of class on this difference. The results indicate significant differences between NESTs and NNESTs in terms of their students' perceived attitudes and motivation with respect to English learning. However, these differences varied depending upon the type of class. These results provide empirical support for the role of the type of class as a variable moderating the effect of the difference between NESTs and NNESTs on students' attitudes and motivation. In addition, the type of class moderated teachers' self-perception of their own teaching practices, providing support for the moderating effect of the type of class on various measures and samples. Theoretical as well as pedagogical implications are discussed.